REMINISCENCES OF ERVIN G ERDÖS - Igić, Rajko (Scripta Medica, 2019)
This article includes personal reminiscence of the great scientist Ervin G Erdös (19222019). Dr Erdös was born in Budapest, where he studied medicine. He finished his medical school in Munich, and obtained MD degree in 1952. There he joined, as a postdoctoral fellow, Professor Eugen Werle who had earlier discovered kallikrein, an enzyme that liberates kinins from kininogen. Dr Erdös continued his work on peptides and peptidases at the universities of Pittsburgh, Oklahoma City, Dallas and Chicago. In his eighties, he retired from the University of Illinois, Chicago. His numerous contributions to science belong to three important areas: 1) enzymes that generate, inactivate, or modulate the activity of kinins and other biologically active peptides, 2) angiotensin-converting enzyme and 3) kinin receptors. These discoveries contributed to our understanding of several bioactive peptide systems. Dr Erdös also found important interactions of the renin-angiotensin and kallikrein-kinin systems.
Keywords: renin; ACE; angiotensin; kallikrein; kinin; peptides